KINEMATIC PARAMETERS OF MAE GERI-KEKOMI IMPACT IN RELATION TO GENERAL AEROBIC ENDURANCE OF KARATISTS - Dragiša Jovanović,; Osman Lačić,; Jasmin Bilalić,; Tarik Huremović,; Eldar Goletić,; Džemal Huremović, (Sport Scientific And Practical Aspects, 2025)
Karate is a martial art dominated by a kind of combination of strength, explosiveness and agility, speed and agility, timeliness, timing and determination. The development of karate as a sport requires innovative technologies and a modern approach to the conceptualization of training and competition patterns and diagnostic procedures aimed at analyzing the structure of anthropological dimensions, their relations and specific influences on sports events. This study was conducted on a sample of karate athletes, senior competitors from karate clubs from the Tuzla Canton, with a total of 16 entities, divided into two groups based on maximum oxygen consumption (VO2max). The entities are male, chronologically aged 18-22, who are in the regular training process and compete in the senior competition of the current system of karate competitions in the Republic of Bosnia and Herzegovina. The kinematic parameters of mae geri-kekomi impact during a three-minute progressive physiological load in relation to general aerobic endurance were monitored. Detection was performed every 30 seconds using KINOVEA 0.8.15 software package, while t-test for dependent samples was applied to determine differences between groups. The kinematic variables monitored were the height of the center of gravity of the body in the kick position, the height of the kick and the speed of the kick. General aerobic endurance was determined using the Shuttle-ran test, and the maximum oxygen consumption (VO2max) in karate was indirectly calculated. The aim of the research is to determine the kinematic parameters of the mae geri-kekomi foot kick and to detect differences in the manifestation of that kick during time zones of 30 seconds as fatigue effects at three minutes of progressive physiological load based on general aerobic endurance of karate